Microbially Enhanced Oil Recovery by Alkylbenzene-Oxidizing Nitrate-Reducing Bacteria - Suri, Navreet; Gassara, Fatma; Stanislav, Paul; Voordouw, Gerrit (Frontiers in Microbiology, 2019)
Microbially enhanced oil recovery (MEOR) of heavy oil and bitumen is challenging because light hydrocarbons, which can feed resident microbial communities are present in low concentrations, if at all. We have recently shown that increasing the toluene concentration of heavy oil by aqueous injection followed by injection of nitrate boosts the activity of toluene-oxidizing nitrate-reducing bacteria in heavy oil-containing sand pack columns, giving production of residual oil in place (ROIP). In the current work we found that ethylbenzene is as effective as toluene. Microbial community analyses indicated Thauera and Pseudomonas to be main components of nitrate-containing batch and continuous cultures, regardless whether ethylbenzene or toluene was used as the electron donor. Biomass from batch cultures grown with heavy oil amended with ethylbenzene or toluene and nitrate or biomass from continuous cultures grown on ethylbenzene or toluene and nitrate had similar MEOR activity. Increasing the concentration of injected biomass from continuous cultures increased the fraction of ROIP recovered both in the absence and in the presence of nitrate. Nitrate increased the fraction of ROIP recovered by about 2-fold by increasing the concentration of biomass in the columns. Emulsification of oil by surface-adhering biomass and blocking of aqueous flow channels by oil emulsion droplets are proposed as a possible mechanism of hydrocarbon- and nitrate-mediated MEOR. Pure isolates Thauera sp. NS1 and Pseudomonas sp. NS2, which used both ethylbenzene and toluene, were obtained but did not offer improved MEOR compared to the use of batch and continuous cultures.